2022
DOI: 10.1007/s12671-021-01808-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 8-Week Mindfulness Course on Affective Polarization

Abstract: Objectives The European Union Brexit referendum has split the British electorate into two camps, with high levels of affective polarization between those who affiliate with the Remain side (Remainers) and the Leave side (Leavers) of the debate. Previous research has shown that a brief meditation intervention can reduce affective polarization, but no study has thus far investigated the effects of an 8-week mindfulness program on affective polarization. This is what will be examined in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Of course, even small effects can be important, particularly when a minimal intervention is involved [ 26 ]. Given that a recent study found that eight weeks of mindfulness training reduced affective polarization among Remainers and Leavers [ 27 ], future studies should examine a larger or potentially more potent dosage of befriending meditation practice (e.g., repeated practice sessions, live instruction). Moreover, the fact that even small effects were detected from a recorded meditation practice supports the possibility of delivery at scale.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, even small effects can be important, particularly when a minimal intervention is involved [ 26 ]. Given that a recent study found that eight weeks of mindfulness training reduced affective polarization among Remainers and Leavers [ 27 ], future studies should examine a larger or potentially more potent dosage of befriending meditation practice (e.g., repeated practice sessions, live instruction). Moreover, the fact that even small effects were detected from a recorded meditation practice supports the possibility of delivery at scale.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an experiment by Berry et al ( 2021 ) found that both trainees in mindfulness and trainees in sham mindfulness (which emphasized relaxation) showed parochial helping for racial in-group members in their everyday lives, although mindfulness meditation alone predicted increases in helping behavior. Moreover, meditative practices have been shown to influence political intergroup bias (Simonsson et al, 2022a , b , c ). For example, relative to a matched mindfulness condition and an active control condition (listening to educational content on mindfulness meditation), a 10-min audio-guided befriending meditation (similar to compassion and loving-kindness meditations) reduced affective polarization, or the difference in feelings that Americans who are affiliated with Democrats or Republicans had toward political in-group members versus for out-group members (Simonsson et al, 2022c ).…”
mentioning
confidence: 99%
“…Sustained mindfulness training may also have the potential to reduce bias in intergroup emotions. An 8-week mindfulness program reduced affective polarization over time more than did a waitlist control condition (Simonsson et al, 2022a ).…”
mentioning
confidence: 99%
“… 18 , 128 For example, mindfulness interventions at the policymaker level may help to improve perspective‐taking, break “status quo” thinking and shift ways in which wellness is achieved at larger scales. 129 , 130 Mindfulness has also been shown to help reduce polarization in the context of political issues, 131 underscoring the value in promoting emotionally intelligent leadership.…”
Section: Promoting a Planetary Health Mindset Is Vital To The Solutionsmentioning
confidence: 99%